Lactobacillus reuteri F‐9‐35 Prevents DSS‐Induced Colitis by Inhibiting Proinflammatory Gene Expression and Restoring the Gut Microbiota in Mice - Sun, Mao‐cheng; Zhang, Fu‐cheng; Yin, Xue; Cheng, Bi‐jun; Zhao, Chang‐hui; Wang, Yan‐ling; Zhang, Zheng‐zhe; Hao, Hong‐wei; Zhang, Tie‐hua; Ye, Hai‐qing (Journal of food science, 2018)
Probiotics are considered to be a potential treatment for ulcerative colitis (UC). The aim of this study was to compare the preventive effect of a space flight‐induced mutant L. reuteri F‐9‐35 and its wild type on UC in vivo. Female mice were randomly assigned to five groups: one normal and four colitic. Mice from colitis groups were daily gavaged with 0.2 mL 12% (w/v) skim milk containing the mutant or wild type (1 × 1011 CFU/mL), skim milk alone or distilled water for the whole experiment period, starting 7 days before colitis induction. UC was induced by administrating mice with 3.5% (w/v) dextran sulfate sodium (DSS) in drinking water for 7 days, after which DSS was removed and maintained for 3 days as a recovery phase. The results showed that the mice fed with L. reuteri F‐9‐35 had less inflammatory phenotype according to macroscopic and histological analysis, reduced myeloperoxidase activity, and lower expression of proinflammatory genes (Tumor necrosis factor‐α, cyclooxygenase‐2 and interleukin‐6) in colonic tissue compared with control. Furthermore, L. reuteri F‐9‐35 protected the mice from gut microbiota dysbiosis from DDS induced colitis. Neither wild type nor the milk alone had such beneficial effects. From above we conclude that L. reuteri F‐9‐35 has great potential in the prevention of UC as a dietary supplement. Practical Application Ulcerative colitis (UC) is the most common inflammatory bowel diseases and there is still a lack of safe and effective treatments. Consumption of L. reuteri F‐9‐35 may effective in preventing human UC.